Social identity and status in the Classical and Hellenistic Northern Peloponnese : the evidence from burials - Dimakis, Nikolas, (Archaeopress archaeology., 2016)
Classical and Hellenistic cemeteries can give us more than descriptions and styles of pottery, art and burial architecture; they can speak of people, societies, social conventions as well as of social distinctions. This book aims to employ and illustrate the unique strengths of burial evidence and its contribution to the understanding of social identity and status in the Classical and Hellenistic Northern Peloponnese.